2005
DOI: 10.1093/ps/84.8.1332
|View full text |Cite
|
Sign up to set email alerts
|

Stocking density effects on growth performance and processing yields of heavy broilers

Abstract: This study examined responses of male broilers during a 49-d production cycle to 4 placement densities in 2 trials. Trials were pooled because no treatment x trial interaction occurred. In each trial, 1,488 male chicks were randomly placed into 32 floor pens to simulate final densities of 30 (37 chicks/pen), 35 (43 chicks/ pen), 40 (50 chicks/pen), and 45 (56 chicks/pen) kg of BW/m2 of floor space based on a projected final BW of 3.29 kg. Growth rate and nutrient utilization were similar (P > or = 0.05) among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
99
2
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(135 citation statements)
references
References 17 publications
23
99
2
11
Order By: Relevance
“…The final body weight results of the present experiment are consistent with those obtained by Dozier et al (2005b), who did not find live weight differences in 32-d-old broilers reared in environmentallycontrolled houses at densities of 9, 11, 12, or 13 birds/ m 2 . In addition, Oliveira et al (2005) and Buijs et al (2009) did not observe any effect of rearing density on that parameter either.…”
Section: Resultssupporting
confidence: 92%
“…The final body weight results of the present experiment are consistent with those obtained by Dozier et al (2005b), who did not find live weight differences in 32-d-old broilers reared in environmentallycontrolled houses at densities of 9, 11, 12, or 13 birds/ m 2 . In addition, Oliveira et al (2005) and Buijs et al (2009) did not observe any effect of rearing density on that parameter either.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, a reduction in access to water and feed, enhancement ammonia and an unfavorable air quality because of insufficient air exchange (Feddes et al, 2002). In addition, Dozier et al (2005) reported that the negative effect of a high stocking density on broiler growth rate is double as the chicks progressed in BW. Under stressors, the behavioral patterns of birds will be changed and Asian J. Anim.…”
Section: Resultsmentioning
confidence: 99%
“…FPD is thought to be caused mainly by litter condition, especially high moisture in the litter [11,17,20,21]. Litter condition involves stocking density [7,8,12,25,26], feedstuff composition [9,12], litter material [15] and housing system [24]. It varies significantly according to the farm management, and therefore, the incidence of FPD at different farms is thought to be uneven.…”
Section: Examination At Slaughterhousesmentioning
confidence: 99%